Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1088/1361-6463/ab5b1b
|View full text |Cite
|
Sign up to set email alerts
|

On the air atmospheric pressure plasma treatment effect on the physiology, germination and seedlings of basil seeds

Abstract: Basil (Ocimum basilicum) seeds were treated for different exposure times with a non-equilibrium plasma produced by a volume dielectric barrier discharge in humid air at atmospheric pressure. Plasma treatment did not change the seed structure and morphology, as visualized by high-resolution computed x-ray microtomography. A faster and higher germination rate was observed with plasma treatment of 1 and 3 min. Plantlets grown in sand, after both 2 and 3 weeks, showed a more developed root apparatus and better bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 58 publications
0
48
0
Order By: Relevance
“…Ambrico et al [50] instead used µ-XRF and showed the concentration and redistribution of macro-and micronutrients such as potassium after plasma treatment. As an example, on the one hand, the diffusion of potassium into the seed interior may improve the germination through enzyme activation, help with water retention, or detoxify ROS [134].…”
Section: Nutrient Absorptionmentioning
confidence: 99%
“…Ambrico et al [50] instead used µ-XRF and showed the concentration and redistribution of macro-and micronutrients such as potassium after plasma treatment. As an example, on the one hand, the diffusion of potassium into the seed interior may improve the germination through enzyme activation, help with water retention, or detoxify ROS [134].…”
Section: Nutrient Absorptionmentioning
confidence: 99%
“…The direct treatment of seeds is predominantly performed with dielectric barrier discharges (DBDs) in ambient air. [ 51,65–92 ] The seeds are, thus, exposed to a variety of long‐ and short‐lived RONS (e.g., O, OH, O 3 , H 2 O 2 , N, NO, NO 2 − , NO 3 − ) and, in the case of volumetric DBDs (VDBD), to ions and the electric field. [ 93 ] Most studies report plasma dose‐dependent increased germination rate, increased root length, and enhanced growth of the seedlings.…”
Section: Germination Seedling Development and Atmospheric Plasma Immentioning
confidence: 99%
“…Transverse sections of basil seeds showed remobilization of some key micro‐ and macronutrients from the cotyledons and endosperm into the embryonic radicle. [ 70 ] The authors suggest that the electric field of their VDBD promotes the element mobilization. Future characterization of the timing of this response will help clarify whether this remobilization is mediated by plant transporters.…”
Section: Germination Seedling Development and Atmospheric Plasma Immentioning
confidence: 99%
“…Among those, the atmospheric pressure low temperature plasma (LTP) represents a novel promising tool 5 . LTPs can be produced with different discharge configurations, such as corona, micro-hollow cathode, gliding arc, atmospheric uniform glow, dielectric barrier discharges, plasma jet and needle [6][7][8][9][10][11][12][13][14] .…”
mentioning
confidence: 99%